Hypoperfusion warm ischaemia time in renal transplants from donors after circulatory death. Issue 9 (31st August 2020) - Kostakis, Ioannis D; Kassimatis, Theodoros; Flach, Clare; Karydis, Nikolaos; Kessaris, Nicos; Loukopoulos, Ioannis
Abstract: Background: The donor hypoperfusion phase before asystole in renal transplants from donors after circulatory death (DCD) has been considered responsible for worse outcomes than those from donors after brain death (DBD). Methods: We included 10 309 adult renal transplants (7128 DBD and 3181 DCD; 1 January 2010–31 December 2016) from the UK Transplant Registry. We divided DCD renal transplants into groups according to hypoperfusion warm ischaemia time (HWIT). We compared delayed graft function (DGF) rates, primary non-function (PNF) rates and graft survival among them using DBD renal transplants as a reference. Results: The DGF rate was 21.7% for DBD cases, but ∼40% for DCD cases with HWIT ≤30 min (0–10 min: 42.1%, 11–20 min: 43%, 21–30 min: 38.4%) and 60% for DCD cases with HWIT >30 min (P < 0.001). All DCD groups showed higher DGF risk than DBD renal transplants in multivariable analysis 0–10 min: odds ratio [OR] 2.686 [95% confidence interval (CI) 2.352–3.068]; 11–20 min: OR 2.531 [95% CI 2.003–3.198]; 21–30 min: OR 1.764 [95% CI 1.017–3.059]; >30 min: OR 5.814 [95% CI 2.798–12.081]. The highest risk for DGF in DCD renal transplants with HWIT >30 min was confirmed by multivariable analysis [versus DBD: OR 5.814 (95% CI 2.798–12.081) versus DCD: 0–10 min: OR 2.165 (95% CI 1.038–4.505); 11–20 min: OR 2.299 (95% CI 1.075–4.902); 21–30 min: OR 3.3 (95% CI 1.33–8.197)]. No significant differences were detected regarding PNF rates (P = 0.713) or graft survival (P = 0.757), which was confirmed by multivariable analysis. Conclusions: HWIT >30 min increases the risk for DGF greatly, but without affecting PNF or graft survival.